Changes in crime-related factors and subjective well-being over time and their mutual relationship - Krulichová, Eva (International journal of law, crime and justice, 2021)
Recently, there has been growing interest in crime-related determinants of subjective well-being (SWB). The existing findings are, however, rather contradictory. The relationship between the aforementioned phenomena is most often examined using cross-sectional data, although it seems their development over time might be interlinked. Moreover, only limited attempts have been made to address the multidimensionality of SWB. Using a pseudo-panel analysis of eight bi-annual waves of the European Social Survey (ESS) consisting of 24 European countries, we examined the relationship between changes in two SWB dimensions-life satisfaction and happiness-and crime-related factors, i.e. victimization experience and feeling of safety, over time. The data showed that both victimization and feeling of safety are important determinants of SWB, although different patterns in the relationship between SWB dimensions and the crime-related factors were revealed.